A comparative study on effects of layered double hydroxide (LDH) and halloysite nanotube (HNT) on the physical, mechanical and dynamic mechanical properties of reed flour/polyvinyl chloride composites. (March 2023) - Ghalehno, Mohammad Dahmardeh; Kord, Behzad; Adlnasab, Laleh
The objective of this research was to comprehensively compare the effects of two different types of nanoclay, namely layered double hydroxide (LDH) and halloysite nanotube (HNT) on the physical, mechanical, and dynamic mechanical properties of compression-molded composite panels fabricated from reed flour (RF) and polyvinyl chloride (PVC). To achieve the desired properties in the composites, the clay nanoparticles were modified with surfactant (mLDH and mHNT) before usage. The results showed that the composite specimens with mLDH exhibited higher tensile and flexural properties (strength and moduli) than with mHNT at low content. Compared with the maximum flexural strength and tensile modulus of 21.56 MPa and 2186.16 MPa for the specimens made with mHNT, the highest flexural strength and tensile modulus were found in the specimens incorporated with mLDH (23.05 MPa and 2227.44 MPa). Moreover, at high content, the composite specimens with mHNT presented greater hydrophobicity. The comparative analysis exhibited that that the water uptake of the composites including mHNT (5.03%) was approximately 15% lower than that of the mLDH (5.73%) based composite. The DMTA results indicated that the composite specimens with mLDH demonstrated better molecular restriction and larger storage modulus than with mHNT. Besides, the loss-tangent (tan δ) peak was shifted to a higher temperature for the samples including both mLDH and mHNT than without ones. The specimens made with mLDH had the highest glass transition temperature values (70.67°C) compared with 70.12°C for the specimens treated with mHNT. Morphological observations showed that the nanoparticles were predominantly dispersed uniformly within the polymer matrix. Overall, it is found that the addition of 3 phc mLDH clay was the most effective in the composite formulation; it has significantly enhanced the properties of the wood-plastic composites.